Connect the dots: connecting problem solving and videogames in initial training of early childhood education teachers - Antequera-Barroso, Juan Antonio; Carmona-Medeiro, Enrique (Frontiers in Education, 2024)
Video games, although not originally designed for educational purposes, have the potential to serve as a significant tool in creating an efficient and motivating learning environment that facilitates the acquisition of mathematical concepts or notions. This study aims to examine the responses provided by students (n=100) majoring in Early Childhood Education to the video game "Connect the dots" concerning the opportunities it offers. These opportunities encompass the knowledge and notions that can be addressed, strategies employed to overcome various stages or levels in comparison to those posed for problem-solving, potential modifications for classroom integration or the exploration of alternative concepts, as well as the emotions evoked in a non-traditional learning environment. The responses were analyzed both qualitatively and quantitatively to gain a deeper understanding of their alignment with the research objectives and questions. Our data show that the students demonstrated the ability to identify the possibilities offered by a video game for classroom application and to envision alternative approaches to mathematical knowledge teaching.